Wirausaha Dalam Meningkatkan Kesejahteraan Ekonomi Masyarakat Di Desa Baderan - Endang Murti; Retno Iswati; Agus Wiyaka (Universitas Merdeka Madiun, 2018)
Entrepreneurship has a strategic role in reducing poverty by creating employment opportunities that people are interested in based on the skills / abilities of each person. Through entrepreneurship, the government can realize more equitable and equitable development for the community to maximize the potential advantages of natural resources. The growth of the village business cannot be separated from the participation of the community and the village government contributing to helping develop the village's potential and business. The main thing done by the village government is to provide easy permits for submitting capital from banks, promoting village potential through events held through village competitions, providing business training, capital assistance and services with related agencies. Then community participation by participating in buying products and promoting the results of the business of developing entrepreneurship.